Concept of scientific wildlife conservation and its dissemination - Zhou, Xue-Hong; Wan, Xiao-Tong; Jin, Yu-Hui; Zhang, Wei (Dōngwùxué yánjiū, 2016)
In recent years, wildlife conservation has attracted great public attention. However, substantial distinctions can be found in the prevailing concepts of wildlife conservation, particularly with the recent notion that emphasizes animal rights. Wildlife welfare and wildlife rights are not synonymous, with welfare more compatible with the reasonable and legal utilization of wildlife. The key to scientific wildlife conservation is the appropriate awareness and appreciation of the relationship between wildlife conservation and utilization and the theoretical basis of holism. Nevertheless, rational biases regarding the public＇s understanding of wildlife conservation and the spread of information via social media still exist. As such, expansion of the concept of scientific wildlife conservation requires the application of several measures. Wildlife conservation researchers should be regarded as the most important disseminators of scientifically-based information, with education in schools and universities of growing importance. Furthermore, the media should shoulder the social responsibility for the accurate dissemination of conservation information.